A new abelisaurid from the Huincul Formation (Cenomanian-Turonian; Upper Cretaceous) of Río Negro province, Argentina. (March 2020) - Cerroni, M.A.; Motta, M.J.; Agnolín, F.L.; Aranciaga Rolando, A.M.; Brissón Egli, F.; Novas, F.E.
Abstract: The record of abelisaurids in South America, particularly Argentina is relatively abundant. However, abelisaurid diversity is far from being well-known. Huincul Formation has yielded diverse theropod remains, including the abelisaurids Ilokelesia and Skorpiovenator . The aim of the present contribution is to describe a new abelisaurid coming from the Upper Section of the Huincul Formation (Cretaceous; Cenomanian-Turonian) at the Violante Farm fossil site, Río Negro province, northern Patagonia, Argentina. The new taxon described in this contribution is represented by an incomplete specimen including well-preserved maxilla and dorsal vertebrae, and distorted pelvic girdle and caudal and sacral vertebrae. Its size, much smaller than large abelisaurids as Abelisaurus and Carnotaurus indicates that the new taxon probably occupied a different ecological niche within the carnivoran guild. Highlights: We describe a new species of Abelisauride from the Huincul Formation (Cenomanian-Turonian), Patagonia, Argentina. Tralkasaurus cuyi nov. gen. et sp. constitutes a new form of medium-sized abelisaurid. The phylogenetic analysis resulted in the nesting of Tralkasaurus as a basal abelisaurid. The new abelisaurid affords new evidence regarding small to medium-sized abelisaurids from Patagonia.